PENGEMBANGAN MODEL OUTDOOR PROJECT-BASED LEARNING BERBASIS EKSPLORASI LINGKUNGAN SEKITAR UNTUK SISWA SEKOLAH DASAR: KAJIAN LITERATUR SISTEMATIS - Kurniawati, Leny; Avrilianda, Decky; Widiarti, Nuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to systematically examine the theoretical and empirical foundations for developing an outdoor project-based learning model centered on the exploration of the surrounding environment for elementary school students. This study employs a systematic literature review method, analyzing 34 articles from the Scopus, Web of Science, ERIC, and Google Scholar databases published between 2021 and 2026. The screening process followed the PRISMA guidelines through the stages of identification, screening, eligibility, and inclusion. Data were analyzed thematically to identify patterns, relationships between variables, and research gaps. The findings indicate that integrating project-based learning with an outdoor learning approach centered on exploring the surrounding environment can enhance students’ active engagement, conceptual understanding, critical thinking skills, and environmental awareness at the elementary school level. This model is rooted in constructivist theory and experiential learning, which emphasize direct experience as the foundation for knowledge construction. Nevertheless, its implementation still faces challenges such as teacher readiness, time constraints, and the complexity of managing out-of-class activities. This study formulates an initial conceptual framework for an environmental exploration-based outdoor project-based learning model that can be further tested in development research.